Consciousness, unconsciousness and death in the context of slaughter. Part II. Evaluation methods. (August 2016) - Terlouw, Claudia; Bourguet, Cécile; Deiss, Véronique
Abstract: This second review describes indicators of consciousness and unconsciousness that can be used in the abattoir. These indicators evaluate different aspects of cerebral functioning, but only indirectly. It is therefore necessary to monitor several indicators. Animals are considered unconscious if signs of consciousness are absent, and signs of unconsciousness are present. Given that the unconscious state may be reversible it is further necessary to monitor these indicators until the end of bleeding. The techniques used to diagnose brain death in humans cannot be used in the slaughterhouse. Under field conditions, at the end of bleeding, the absence of breathing and of brainstem reflexes and the adequacy of the exsanguination are verified. If these three aspects are confirmed, in the context of the slaughterhouse and at this stage of the slaughter process the loss of vital functions is irreversible and the animal can be considered dead. Highlights: Indicators of consciousness and unconsciousness indirectly evaluate different aspects of cerebral functioning. It is necessary to monitor several indicators until the end of bleeding. Before further processing the animal, breathing and of brainstem reflexes must be absent and the exsanguination complete.